Correlation between PD-1 and sPD-L1 expression levels in peripheral blood of DLBCL patients and their clinicopathological characteristics: PD-1 and sPD-L1 correlation in DLBCL patients - Wang, Liang; Cao, Congcong; Qiu , Juan; Zhang, Jianing; He, Qiang; Song, Lihua; Xie, Linna; Ma, Ji (Cellular and Molecular Biology, 2024)
Molecular pathology and clinical characteristics play a crucial role in guiding treatment selection and predicting the prognosis of diffuse large B-cell lymphoma (DLBCL). The programmed cell death protein 1 (PD-1) and its ligand (PD-L1), have emerged as pivotal regulators of immune checkpoints in cancer. The objectives of this study are to investigate the correlation between the expression levels of PD-1 and soluble PD-L1 (sPD-L1) in the peripheral blood of DLBCL patients, analyze their clinicopathological characteristics, and identify the optimal beneficiary group for PD-1/PD-L1 blockade. Peripheral blood samples were collected from 36 DLBCL patients before their initial treatment at Shandong Cancer Hospital between December 2018 and July 2019. The expression levels of PD-1 and sPD-L1 were measured using flow cytometry and enzyme-linked immunosorbent assay (ELISA), respectively. The clinicopathological characteristics, including age, sex, Ann Arbor stage, International Prognostic Index (IPI) score, response to treatment, etc., were recorded for each patient. The surface expression of PD-1 on peripheral blood T cells was significantly higher in DLBCL patients compared to healthy controls. There was a significant association between elevated PD-1 expression levels and the advanced Ann Arbor stage (P=0.0153) as well as the B group (P=0.0184). Higher sPD-L1 levels were associated with the GCB subtype according to Hans's classification (P=0.0435). The expression levels of PD-1 and sPD-L1 in the peripheral blood of DLBCL patients are significantly correlated with advanced disease stage, B group, and GCB subtype according to Hans's classification. This suggests that the PD-1/PD-L1 axis play a critical role in specific subgroups of DLBCL. Targeting this axis could serve as a potential therapeutic strategy to enhance the clinical outcomes of DLBCL patients. Further studies are necessary to explore the prognostic implications of PD-1 and sPD-L1 expression levels in DLBCL patients.